PENINGKATAN PENGETAHUAN IBU ANAK USIA DINI MELALUI PENDIDIKAN KESEHATAN TENTANG PENCEGAHAN STUNTING - Atik Aryani; Lut Fika Daru Azmi; Widiyono Widiyono; Ni'mah Mufidah (Universitas Mataram, 2026)
Stunting in young children is a chronic malnutrition problem that can lead to growth failure due to a prolonged lack of nutrient intake. The effects of stunting can increase the risk of illness, impaired brain and mental development, and delayed motor development in children. A mother’s lack of knowledge can put her child at risk of stunting. A mother’s education and knowledge play a significant role in preventing stunting; therefore, health education and awareness-raising programmes are essential. The objective of this activity is to enhance mothers’ knowledge regarding the prevention of stunting in young children. The target group comprises 36 mothers of young children at the ‘Aisyiyah Bustanul Athfal Kindergarten, Mandong, Trucuk, Klaten. The results of the community service activity showed that, following the provision of health education on stunting, the participants’ knowledge improved. The average pre-test score was 78.75 and the post-test score was 95.84. The community service activity ran smoothly; the participants were enthusiastic and eager to take part in the health awareness session on the prevention of stunting in children